Molecular Biological Approach of Crocus sativus L. and its Allies - Zubor, Ákos; Surányi, Gyula; Győri, Zoltán; Borbély, György; Prokisch, József (Acta Agraria Debreceniensis, 2004)
The hay saffron (Crocus sativus L.) is a sterile triploid plant, known in human culture only, with no fertile seeds produced. The origin of saffron is still a mist, however it is assumed to be an autopoliploid mutant or a hybrid. The recent classification and most of the former taxonomic publications define C. sativus to be derived from C. cartwrightianus, a wild species. Because of the sterility of hay saffron it seemed to be reasonable to apply molecular biological methods to complete classical taxonomic studies in examining its relations. The DNA polymorphism based AFLP method has confirmed the close relationship between these species.